2008
DOI: 10.1080/14616730701868589
|View full text |Cite
|
Sign up to set email alerts
|

Independent influences upon mother–toddler role reversal: infant–mother attachment disorganization and role reversal in mother's childhood

Abstract: In role reversal a child takes an inappropriate parental, spousal, or peer role with the caregiver. The study assessed attachment disorganization with mother in infancy in the Strange Situation (Ainsworth, Blehar, Waters, & Wall, 1978) and role reversal at 2 years old in videotaped mother-child interactions. By closely observing role reversal at this early age, results fill in the picture concerning the link between disorganized infant-mother attachment and controlling role reversal at 6 years old (Main & Cass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
(34 reference statements)
1
29
0
2
Order By: Relevance
“…Further, mothers at high-risk for abuse were significantly less likely to successfully repair with their children once a rupture had occurred. These findings converge with other studies of parenting-at-risk that have observed patterns of role reversal in maltreating and other at-risk parent-child dyads, whereby children act in a caregiver role with their parents (e.g., Dean, Malik, Richards, & Stringer, 1986; Macfie et al, 2005, 2008). Others have observed that depressed mothers make infrequent efforts to repair following their toddlers’ interactive ruptures (e.g., Jameson et al, 1997; Rocissano et al, 1987).…”
Section: Studysupporting
confidence: 89%
“…Further, mothers at high-risk for abuse were significantly less likely to successfully repair with their children once a rupture had occurred. These findings converge with other studies of parenting-at-risk that have observed patterns of role reversal in maltreating and other at-risk parent-child dyads, whereby children act in a caregiver role with their parents (e.g., Dean, Malik, Richards, & Stringer, 1986; Macfie et al, 2005, 2008). Others have observed that depressed mothers make infrequent efforts to repair following their toddlers’ interactive ruptures (e.g., Jameson et al, 1997; Rocissano et al, 1987).…”
Section: Studysupporting
confidence: 89%
“…Interventions designed specifically for mothers with BPD and their children do not exist. However, authors have made general recommendations favoring attachment therapies (c.f., Macfie, Fitzpatrick, Rivas, & Cox, 2008), especially during infancy through the preschool period and/or psychoeducation-based interventions (c.f. Gunderson, Berkowitz, & Ruiz-Sancho, 1997) for family members of those with BPD.…”
Section: Current Interventionsmentioning
confidence: 99%
“…The infant is unable to find security in the relationship, and is caught between approach and avoidance and disorganizes under stress. To gain some feeling of security in the relationship, this child may develop a parent–child role reversal that has thus far been observed both in the toddler period (Macfie, Fitzpatrick, Rivas, & Cox, 2008) and at age 6 (Main et al, 1985). Moreover, role reversal in the toddler period in turn predicts behavior problems in kindergarten (Macfie, Houts, McElwain, & Cox, 2005) and is transmitted intergenerationally (Macfie, McElwain, Houts, & Cox, 2005).…”
Section: Internal Working Modelsmentioning
confidence: 99%